Mechanical properties of mung beans [Vigna radiata (L.) R. Wilczek] after drying and during hermetic storage - SIQUEIRA, Valdiney Cambuy; CANASSA, Ariély Leite; CRIPPA, Diogo Santos; SCHOENINGER, Vanderleia; MABASSO, Geraldo Acácio; MARTINS, Elton Aparecido Siqueira; TOLEDO, Mariana Zampar; TAKAGI, Allan Dellon Alegre (Food Science and Technology, 2024)
Mung beans, a grain legume of Asian origin primarily cultivated for human consumption, are rich in proteins, vitamins, and minerals. Handling these grains during harvest and post-harvest can significantly impact their mechanical properties, which are critical for designing machinery for pod shelling, processing, and grinding. This study aimed to assess the mechanical properties of mung bean grains after drying and during storage in a hermetic environment. The grains were manually harvested and threshed at approximately 15% moisture content (wb). They were then dried in an experimental fixed-bed convective dryer at temperatures of 40 and 50 °C with an air speed of 1.0 m s-1 until a final moisture content of 11.5 ± 0.3% (wb) was achieved. Post-drying, the grains were stored in 200 mL polyethylene terephthalate bottles covered with aluminum foil in a laboratory setting, with analyses conducted every 60 days over 180 days. Results showed that neither the drying temperatures of 40 and 50°C nor the storage duration of 180 days affected the rupture force, deformation, absorbed energy, modulus of toughness, or hardness of the mung bean grains.